Challenging narratives, capturing memories: the Photographic Walk for Gender Diversity on Wikimedia Commons as a practice of public history in university outreach (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article presents the experience of planning and carrying out the Photographic Walk for Gender Diversity on Wikimedia Commons, a public history and university extension initiative aimed at expanding LGBT+ representation in Wikimedia projects. The event, held in downtown Florianópolis, sought to document and upload images of the LGBT+ community’s memory sites, promoting visibility and digital heritage preservation. Based on this experience, we discuss the challenges and lessons learned in organizing Wikimedia-related events, reflect on the relationship between extension and research, and analyze the photo walk as a practice that connects memory, urban space, and community engagement.
Keywords: photo walk; LGBT+ history; gender diversity; public history; Wikimedia Commons